Principles of athletic training a guide to evidence-based clinical practice - Prentice, William E. (McGraw-Hill Education, 2017)
Principles of athletic training: a competency-based approach is designed to be used by athletic trainers in courses concerned with the scientific, evidence-based and clinical foundations of athletic training and sports medicine. The text leads the student from general foundations to specific concepts relative to injury prevention, evaluation, management, and rehabilitation.